Analisis Pengaruh Kurs Dollar, Harga Serat Kapas Dunia, dan Ekspor Tekstil Terhadap Impor Serat Kapas di Indonesia - simanjuntak, wanda; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
The aims of this study is to determine how the impact of the the three variables tahat become the research object that the dollar exchange rate, the world price of cotton fiber and textile exports againts imports of cotton fiber in Indonesian. The study use secondary data in the 1995-2014 period. The technique of analyzing data use multiple linear regression by using SPSS 16.00 program which was equipped with the classical assumption test and standardized coeficient beta. Besed on the results of the test analysiis, it was found simultaneously that the three independent variables have a significant influence to the import of cotton fiber in Indonesian. Partially the dollar exchange rate, the world price of cotton fiber had a significant negative impact to the imports of cotton fiber in Indonesian, while textile exports gave positive impact. In addition, the dollar exchange rate was the independent variable that has dominant influence towards the import of cotton fiber in Indonesian from analysis of standardized coeficient beta.
Keywords: ekspor tekstil; harga serat kapas dunia; impor serat kapas; kurs dollar